Participatory Budgeting and Community Development: A Global Perspective. (April 2023) - Touchton, Michael; McNulty, Stephanie; Wampler, Brian
Participatory budgeting (PB) is designed to leverage local knowledge about community needs and translate spending preferences into tangible community development action by giving communities control over key budgetary resources. Moreover, PB participants learn about decision-making processes in development policy and can organize to pursue their communities' interests beyond the PB process by engaging with government and civil society. PB advocates hope that infrastructure, service delivery, and, ultimately, well-being will improve for underserved communities and groups that have been historically excluded from the perspective of representative democracy. This article presents the theoretical logic connecting PB to community development and summarizes the global evidence from studies that test the theoretical propositions above. We find evidence for PB's impact on community development performance in several important contexts. However, we also note that many hypotheses have yet to be tested in rigorous, large-N, comparative studies. There is thus considerable room to evaluate PB's impact in the future.